Pharmaceutical adaptation faced with the new health challenges arising by Сovid 19 in Algeria: trend of development for pharmaceutical management - Jou, Siham; Datoussaid, Aimad; Ezzine, Abdelmadjid; Hamadi, Abdelkader (Management and Entrepreneurship: Trends of Development, 2024)
The objective for this paper is to determine the extent to which pharmacists are adapting to the growing needs of customers at the covid-19 era. Both pharmacists and their clients are submitted to five challenges: spread of infections, access to medicines, self-medication, work management and staff training. In order to do so, an online case study using a semi-structured interview concerning the main challenges faced by 50 pharmacies during the covid-19 period to describe the role of pharmacies and discuss their future functions was conducted during the months of September/November 2023 in the region located in the far west of Algeria. Then, to measure the degree of urgency and importance of the challenges encountered, we adopted the Eisenhower matrix while using the Likert scale (of 05 choices) with the help of Sphinx plus software. We then applied the same analysis tool to a sample of 138 customers to reveal their degree of pharmaceutical adaptation. This study revealed a high degree of adaptation in terms of (importance/urgency) of pharmacies in relation to their customers for the five challenges mentioned above: (4.94-4.98) / (5/5) for the spread of infections; (4.56-4.94) / (3.97-4.57) for access to medicines; (3.98/1.66) against (3.88-1.54) for self-medication.  (1.60-3.38) versus (1.57-3.39) for work management and (3.40-1.66) versus (3.46-1.37) for training. These results converge towards a concept of pharmaceutical adaptation, which is a trend of development for innovation in pharmaceutical management.JEL Classification: H12, M12